Studies on Ion-Solvent and Ion-Ion Interactions and Adiabatic Compressibilities of Some Bromide Salts in Methanol at Different Temperatures - Choudhury, Ankan; Roy, Mahendra Nath (Biological Sciences - PJSIR, 2005)
The densities, viscosities and ultrasonic speeds of some tetraalkyl and monovalent electrolytes, such as tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, lithium bromide, sodium bromide and ammonium bromide, have been determined in methanol at 303, 308, 313, 318 and 323 K. The limiting apparent molar volumes (V 0 ) and experimental slopes (S *), supplemented with density data, have been interpreted in terms of f v solute-solvent and solute-solute interactions, respectively. The parameters B and A, obtained from the viscosity data analyzed using the Jones-Dole equation, have also been interpreted in terms of solute-solute and solute-solvent interac- tions, respectively. The results show that these electrolytes have structure-making capacities in this solvent. The com- pressibility data supplemented with the ultrasonic speeds explain the electrostriction of the solvent molecules around the positive ions.